Respostas

2013-10-30T15:45:35-02:00
Ambas são equações de 2 grau sendo assim resolvemos pela fórmula de Bhaskara ou pela relações de Girard:
a0
Δ = b² -4ac
Δ = 6² -4 *1 * 9Δ = 36 -36
Δ = 0
x' = (-b + √∆)/ 2a
(-6 + 0)/2 * 1
(-6 + 0)/2
-6/2= -3
x'' = (-b - √∆)/ 2a
(-6 - 0)/2 * 1
(-6 - 0)/2
-6/2= -3

b) Δ = b² -4ac
Δ = 12² -4 *1 * (-11)
Δ = 144 + 44Δ = 188
x' = (-b + √∆)/ 2a
(-12 + 13,7113092008021)/2 * 1
(-12 + 13,7113092008021)/2 
1,71130920080209/2
= 0,855654600401044
x'' = (-b - √∆)/ 2a
(-12 - 13,7113092008021)/2 * 1
(-12 - 13,7113092008021)/2
-25,7113092008021/2
= -12,855654600401